2016
DOI: 10.1002/bem.22001
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of repetitive transcranial magnetic stimulation (rTMS) in patients with chronic low back pain

Abstract: The objective of the present study was to assess the benefits of 1-week repetitive transcranial magnetic stimulation (rTMS) in patients with chronic low back pain (LBP). The visual analogue scale (VAS), Short Form McGill pain questionnaire (SF-MPQ), and Short Form 36 Health Survey were used to evaluate the effect of this treatment. Eighty-two patients diagnosed with LBP were divided randomly into three groups: rTMS-treated group, sham group, and physical therapy-treated group. We observed a significant reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 67 publications
1
36
0
4
Order By: Relevance
“…Chronic LBP may provoke extreme suffering and deteriorate patient QoL. Abnormal postural control of the trunk muscles may contribute to this condition, and the M1 is assumed to have a critical role in postural control modulation (96,126).…”
Section: Low Back Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic LBP may provoke extreme suffering and deteriorate patient QoL. Abnormal postural control of the trunk muscles may contribute to this condition, and the M1 is assumed to have a critical role in postural control modulation (96,126).…”
Section: Low Back Painmentioning
confidence: 99%
“…Our search located three studies, including one RCT (96) and two case studies (95,97) that focused on the use of rTMS to treat LBP. In 2016, Ambriz-Tututi et al (96) conducted an RCT to investigate the effectiveness of rTMS in patients with chronic LBP.…”
Section: Low Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambriz-Tutut et al (2016) removed a subject due to "poor compliance", however they do not explicitly describe their definition of adherence [30]. Malavera et al (2016) excluded participants that missed one or more day(s) of stimulation [31].…”
Section: Painmentioning
confidence: 99%
“…In addition, there are currently very few published studies to evaluate the efficacy of rTMS in patients with CLBP. A recently published study by Ambriz-Tututi et al demonstrates that 1-week of rTMS therapy produces long-term pain relief in patients with CLBP, without any side effects [9]. Moreover, the results of a case study confirmed the clinical efficacy of rTMS in treating chronic pain-associated depression and insomnia in two patients with CLBP [10].…”
mentioning
confidence: 91%